Blood Oxygen Saturation Measurement Using Polarization-Dependent Optical Sectioning - Mishra, Deepak; Priyadarshini, Neha; Chakraborty, Supriya; Sarkar, Mukul (IEEE sensors journal, 2017)
Blood oxygen saturation (SpO 2 ) measurement is a routinely performed clinical procedure involved in the diagnosis of several critical diseases. However, the most commonly used SpO 2 measuring device, known as oximeter, becomes unreliable in the absence of proper body contact. A non-contact, noninvasive, real-time device is desirable for accurate measurement and continuous monitoring of SpO 2 . This paper presents a polarized imaging-based integrated solution for SpO 2 measurement. The polarization filters are used to separate light components reflecting from deep and superficial layers of skin. The ratio of intensities of the two components is found to have a linear relationship with SpO 2 levels. In contrast to the existing SpO 2 measurement techniques, the proposed method uses a single light source. The experiments are performed with 15 human subjects (11 male and 4 female) using different wavelengths of light. A statistically significant relationship is observed between SpO 2 and the intensity ratios for red light (correlation coefficient r = 0.6426 with p=0.001965 and mean error = 0.0626). The experiments are repeated using white light, and a similar relationship is observed (r = 0.5603 with p = 0.00947 and mean error = -0.9289). Furthermore, the Bland-Altman analysis shows that the results of the proposed method are consistent with the reference data. This suggests that a real-time integrated polarized imaging-based SpO 2 measurement device can be developed based on the proposed method.